2021
DOI: 10.1039/d1ra03912a
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the dielectric constant of BaTiO3–polymer nanocomposites by a developed Paletto model

Abstract: A developed model for estimating the dielectric permittivity of BaTiO3–polymer nanocomposites is proposed by considering the influence of the interphase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…Conversely, there is a significant difference between the dielectric constant of the nanocomposite with varying dielectric constants of the polymer matrix, thus indicating that the dielectric property of the nanocomposite is indeed affected by the dielectric constant of the polymer matrix and nanoparticles, although the polymer matrix dielectric property plays a dominant role in this regard. These research results are consistent with the findings of the reported studies. , …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Conversely, there is a significant difference between the dielectric constant of the nanocomposite with varying dielectric constants of the polymer matrix, thus indicating that the dielectric property of the nanocomposite is indeed affected by the dielectric constant of the polymer matrix and nanoparticles, although the polymer matrix dielectric property plays a dominant role in this regard. These research results are consistent with the findings of the reported studies. , …”
Section: Resultssupporting
confidence: 93%
“…These research results are consistent with the findings of the reported studies. 39,40 As previously reported, the properties of nanoparticles, for example, the size and volume fraction, have an important effect on the dielectric constant of nanocomposites. 36 This conclusion is supported by this study as well.…”
Section: ■ Model Developmentmentioning
confidence: 80%